Traditional values that sustain agroecological coffee production among small scale coffee-growing families in Chiapas, Mexico - Morales-Mendoza, Mónica G.; Herrera, Obeimar B.; Soto-Pinto, María Lorena; Zamora-Lomeli, Carla; Pérez-Akaki, Pablo (Frontiers in Agronomy, 2025)
The objective of the research was to identify the values that indigenous coffee peasant households live and analyse why organized indigenous peasant households continue to produce organic and fair-trade coffee despite the cyclical problems and economic challenges. This research is based on a qualitative approach using participant observation with field notes; mixed interviews such as in-depth semi-structured interviews with a dialogical approach; images; and social cartography to identify symbolism. The results show the values that peasant families live by and the reasons for continuing and preserving organic coffee cultivation in the Tzeltal coffee-growing region of Chiapas: symbolic and intangible values such as the value of legacy, the coffee-growing tradition, the eternal rest of family members in the coffee plantation, the hedonic values in the management of the coffee agroecosystem and love for the land, as well as collective work. In addition, the tangible values of use and exchange were identified for the annual economic income represented by the collective sale of the crop. These values, as part of the socio-cultural component in coffee production, are a central axis in the agroecological transition because they strengthen the principles of agroecology.